2017
DOI: 10.18203/2394-6040.ijcmph20173344
|View full text |Cite
|
Sign up to set email alerts
|

Association between socio-demographic characteristics and preventable lifestyle related risk factors of non-communicable diseases among adolescents: a school based study in Berhampur, Odisha

Abstract: Background: Currently, the health scenario is riddled with the burden of non-communicable diseases. Life style related risk factors established during adolescents may extend into adulthood and may increase risk for non-communicable diseases. So this study was undertaken to ascertain the association of life style related risk factors for Non communicable diseases and socio demographic characteristics among adolescents.Methods: A cross-sectional study was conducted in Berhampur, Odisha. A total of 400 school chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…Patients with a history of alcohol consumption were 36% less likely to have good recommended healthy lifestyle modi cation practices for hypertension than patients with no history of ever alcohol consumption. This nding aligns with a study from India (2), a study conducted in southeastern Nigeria (34), a schoolbased study in Berhampur, Odisha (35), and Kedah in Malaysia (36), and a study conducted in northwestern Nigeria (29). A possible explanation may be that patients who do not seek alcohol consumption are more likely to change their lifestyles by not wasting their time on alcohol addiction.…”
Section: Discussionsupporting
confidence: 89%
“…Patients with a history of alcohol consumption were 36% less likely to have good recommended healthy lifestyle modi cation practices for hypertension than patients with no history of ever alcohol consumption. This nding aligns with a study from India (2), a study conducted in southeastern Nigeria (34), a schoolbased study in Berhampur, Odisha (35), and Kedah in Malaysia (36), and a study conducted in northwestern Nigeria (29). A possible explanation may be that patients who do not seek alcohol consumption are more likely to change their lifestyles by not wasting their time on alcohol addiction.…”
Section: Discussionsupporting
confidence: 89%
“…Both age and gender were found to be significantly associated with passive smoking. This finding is in line with the study on health risk factors in adolescents in India (n = 400) in which age is strongly associated with passive smoking [9]. Additionally, a study in China (n = 9788 non-smoking women) showed that the prevalence of passive smoking among non-smoking women in Jilin Province was 60.6% and 42.9% reported that they were exposed to cigarette smoking at home [10].…”
Section: Demographic Characteristics Of Passive Smokerssupporting
confidence: 88%
“…Linkages between lifestyle behaviours and socio-demographic characteristics had been studied previously mostly by analysing individual’s lifestyle health risk behaviours [ 22 26 ]. The only study for India which estimated the association between aggregation of health risk factors was based only on six selected states (Assam, Karnataka, Maharashtra, Rajasthan, Uttar Pradesh and West Bengal) in the country and the results were generalized for India as a whole [ 27 ].…”
Section: Introductionmentioning
confidence: 99%